Pre-Clinical Assessment of Immune Responses to Adeno-Associated Virus (AAV) Vectors - Basner-Tschakarjan, Etiena; Bijjiga, Enoch; Martino, Ashley T. (Frontiers in Immunology, 2014)
Transitioning to human trials from preclinical models resulted in the emergence of inhibitory AAV vector immune responses which has become a hurdle for sustained correction. Early animal studies did not predict the full range of host immunity to the AAV vector in human studies. While pre-existing antibody titers against AAV vectors has been a lingering concern, cytotoxic T-cell (CTL) responses against the input capsid can prevent long-term therapy in humans. These discoveries spawned more thorough profiling of immune response to rAAV in pre-clinical models, which have assessed both innate and adaptive immunity, and explored methods for bypassing these responses. Many efforts towards measuring innate immunity have utilized Toll-Like Receptor (TLR) deficient models and have focused on differential responses to viral capsid and genome. From adaptive studies, it is clear that humoral responses are relevant for initial vector transduction efficiency while cellular responses impact long-term outcomes of gene transfer. Measuring humoral responses to AAV vectors has utilized in vitro neutralizing antibody (NAb) assays and transfer of seropositive serum to immunodeficient mice. Overcoming antibodies using CD20 inhibitors, plasmapheresis, altering route of delivery and using different capsids have been explored. CTL responses were measured using in vitro and in vivo models. In in vitro assays expansion of antigen-specific T cells as well as cytotoxicity towards AAV transduced cells can be shown. Many groups have successfully mimicked antigen-specific T cell proliferation, but actual transgene level reduction and parameters of cytotoxicity towards transduced target cells has only been shown in one model. The model utilized adoptive transfer of capsid specific in vitro expanded T-cells isolated from immunized mice with LPS as an adjuvant. Finally, the development of immune tolerance to AAV vectors by enriching regulatory T-cells has also been explored as well as modulating t